An international comparison of the cost of fluid resuscitation therapies. Issue 1 (January 2021) - Taylor, Colman; Yang, Li; Finfer, Simon; Machado, Flavia R.; YouZhong, An; Billot, Laurent; Bloos, Frank; Bozza, Fernando; Cavalcanti, Alexandre Biasi; Correa, Maryam; Du, Bin; Hjortrup, Peter B.; et al.
Abstract: Objective: Fluid resuscitation is a ubiquitous intervention in the management of patients treated in the intensive care unit, which has implications for intensive care unit resourcing and budgets. Our objective was to calculate the relative cost of resuscitation fluids in several countries to inform future economic evaluations. Methods: We collected site-level data regarding the availability and cost of fluids as part of an international survey. We normalised costs to net present values using purchasing power parities and published inflation figures. Costs were also adjusted for equi-effective dosing based on intravascular volume expansion effectiveness and expressed as US dollars (USD) per 100 mL crystalloid equivalent. Results: A total of 187 sites had access to cost data. Between countries, there was an approximate six fold variation in the cost of crystalloids and colloids overall. The average cost for crystalloids overall was less than 1 USD per 100 mL. In contrast, colloid fluids had higher average costs (59 USD per 100 mL). After adjusting for equi-effective dosing, saline was ∼27 times less costly than albumin (saline: 0.6 USD per 100 mL crystalloid equivalent; albumin 4–5%: 16.4 USD; albumin 20–25%: 15.8 USD) and ∼4 times less costly than hydroxyethyl starch solution (saline: 0.6 USD; hydroxyethyl starch solution: 2.5 USD). Buffered salt solutions, such as compound sodium acetate solutions (e.g., Plasmalyte®), had the highest average cost of crystalloid fluids, costing between 3 and 4 USD per 100 mL. Conclusion: The cost of fluid varies substantially between fluid types and between countries, although normal (0.9%) saline is consistently less costly than colloid preparations and some buffered salt solutions. These data can be used to inform future economic evaluations of fluid preparations.